2014
DOI: 10.1080/19648189.2014.929538
|View full text |Cite
|
Sign up to set email alerts
|

Compressive behaviour of concrete elements confined with GFRP-prefabricated bonded shells

Abstract: In this paper, a new technique is proposed to confine concrete columns using GFRPprefabricated bonded shells and a shrinkage-compensating cement mortar. The confinement is performed with three identical shells, each of which contains two stepped lap joints at their ends. The main advantage of this technique is that the shells can be directly assembled on site by structural bonding to cover any column shape. The gap between the shells and the column is filled with shrinkage-compensating cement mortar. To evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 13 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Moreover, the jackets are heavy and spread across the concrete and steel, adding weight to the repaired structures, and causing seismic occurrences to attract greater loads as separated components improve their strength [8]. It is also difficult, labor-intensive, and costly to implement these old underwater repair solutions.…”
Section: Figure 1 Differences Between Normal Pile and Interlock Pilejaxmentioning
confidence: 99%
“…Moreover, the jackets are heavy and spread across the concrete and steel, adding weight to the repaired structures, and causing seismic occurrences to attract greater loads as separated components improve their strength [8]. It is also difficult, labor-intensive, and costly to implement these old underwater repair solutions.…”
Section: Figure 1 Differences Between Normal Pile and Interlock Pilejaxmentioning
confidence: 99%
“…The degree of improvement in the axial strength and strain capacities of concrete columns due to the confinement with FRP materials depends on many parameters such as slenderness ratio of columns, shape of cross-section, concrete strength, method used to manufacture the tube, fibre properties, fibre orientation and FRP thickness [9].…”
Section: Effect Of Different Parameters On the Degree Of Confinementmentioning
confidence: 99%
“…Beddiar et al [9] improved the first method by assembling three GFRP sheets made from twill weave glass with structural bending to modify the cross section of square concrete columns and then, filled the gap with shrinkage compensating cement mortar ( Figure 2). The test results confirmed that strength and ductility capacities of noncircular concrete sections can be improved through cross section modifications.…”
Section: Shape Of the Concrete Columnsmentioning
confidence: 99%